Role of Women Workers at Dairy Farms in Banyumas District - Mastuti, S; Hidayat, NN (ANIMAL PRODUCTION, 2009)
Dairy farm is one of promising to increase the household income. Dairy farm generally involve all the household members. The research was aimed to: 1) know contribution of work duration of women woker to the total duration of work in dairy farm; 2) identify contribution of women income to the total income of dairy farm; 3) determine factors that influence contribution of income of women to the total income of dairy farm.  Three sub districts were taken as area sample  using purposive sampling method based on number of dairy farm that utilize women as worker in their farm activities. Sixty seven famers were taken as respondents is this research. Multiple linear regression analysis was used to determine factors that influence contribution of income of women to the total income.  The result showed that: 1) contribution of working duration of women was 25,24 percent; 2) contribution of income of women was Rp 2,762,755.96: and 3) partially, contribution of income of women was influenced by farm scale and dependency ratio. In conclusion, women wokers have contribution on the total duration of work and income; and dairy farm scale and Dependency Ratio influencing contribution of women income. (Animal Production 11(1): 40-47 (2009) Key Words: dairy farm, duration of work, income, role of women